Integrating DNA damage repair with the cell cycle - Murray, Johanne M; Carr, Antony M (Current opinion in cell biology, 2018)
DNA is labile and constantly subject to damage. In addition to external mutagens, DNA is continuously damaged by the aqueous environment, cellular metabolites and is prone to strand breakage during replication. Cell duplication is orchestrated by the cell division cycle and specific DNA structures are processed differently depending on where in the cell cycle they are detected. This is often because a specific structure is physiological in one context, for example during DNA replication, while indicating a potentially pathological event in another, such as interphase or mitosis. Thus, contextualising the biochemical entity with respect to cell cycle progression provides information necessary to appropriately regulate DNA processing activities. We review the links between DNA repair and cell cycle context, drawing together recent advances.